2019
DOI: 10.3389/fpubh.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Examining Pregnancy Related Socio-Cultural Factors Among Adolescent Girls in the Komenda-Edina-Eguafo-Abrem Municipality in the Central Region of Ghana: A Case-Control Study

Abstract: Background and Purpose: Given that Ghana continues to record higher rates of adolescent pregnancy among rural dwellers, notably, those living in the Brong Ahafo, Central and Volta regions, it is surprising that scholarly information related to socio-cultural determinants of this sequel in these mentioned areas of the country is limited. This study sought to examine the socio-cultural factors associated with pregnancy among adolescent girls in Komenda-Edina-Eguafo-Abrem (KEEA) Municipality in the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…This may also be due to incomplete pelvic growth and possibly synchronization of pregnancy and puberty development. These consequences have also been shown in previous studies [22,23]. Adhikari et al 2009 also found that women who married under the age of 18 had more unwanted pregnancies than other women [24].…”
Section: Discussionsupporting
confidence: 83%
“…This may also be due to incomplete pelvic growth and possibly synchronization of pregnancy and puberty development. These consequences have also been shown in previous studies [22,23]. Adhikari et al 2009 also found that women who married under the age of 18 had more unwanted pregnancies than other women [24].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, sociocultural norms surrounding sexuality and reproductive health issues (SRH) in typical Ghanaian and other sub-Saharan homes should not be underestimated. The culture of silence or openness (i.e., obtaining information, discussions, and expressions) between parents and their adolescent girls on sexuality issues can inversely be connected to the onset of sexual debut and subsequent negative implications (e.g., pregnancy, abortions) and vice versa (16,43). Within local set-ups, many adolescent girls have few opportunities to express themselves without prejudice, trust people and places to solicit for sexual information and support.…”
Section: Discussionmentioning
confidence: 99%
“…The study population included female adolescents (15)(16)(17)(18)(19) years in the KEEA Municipality. A sum of 7,667 females (10-19 years), including both pregnant and non-pregnant adolescents represented the study population (50).…”
Section: Population and Samplingmentioning
confidence: 99%
See 2 more Smart Citations